JURISDICTIONAL ISSUES OF INTERNATIONAL INVESTMENT DISPUTE RESOLUTION I N ICSID ARBITRATION - Nora Afriyani; Lena Farsia (Universitas Syiah Kuala, 2022)
This article examines the jurisdictional of ICSID Arbitration and the dispute resolution mechanism of Churchill Mining plc and Planet Mining pty ltd against Indonesia at ICSID. This research is in the form of normative legal research conducted by collecting legal materials. Legal materials are collected using the literature study method by collecting legal materials and information in primary, secondary, and tertiary legal materials. According to Article 25 of ICSID Convention, dispute arising directly from an Investment, absolute requirement of jurisdiction is the existence of a legal dispute. The general secretariat serves as a screening and checks whether the request for arbitration is outside the center's jurisdiction because it is not related to investment. ICSID should no longer need to carry its competency test for too long because both parties have made a contract in determining the choice of forum at ICSID.